Toward ‘Fugitivity as Method’: An Introduction to the Special Issue - Gross-Wyrtzen, Leslie; Moulton, Alex A. (ACME, 2023)
Recent studies on fugitivity, marronage, and other forms of flight from racial violence and dehumanization have mapped a historical and spatial archipelago of Black and Indigenous freedom struggles across the Caribbean and the Americas. Narratives of fugitivity recuperate the diverse and widespread practices of resistance and refusal that have always accompanied racial violence in these geographies. While scholars have demonstrated the ongoing-ness of racial violence from the plantation to the present, studies on fugitivity remain largely confined to the historical period of chattel slavery, having the unintended effect of rendering plantation futures hegemonic in the present. In addition, the majority of studies have confined analysis to the “New World” despite the prevalence of fugitive practices in other spaces of colonial and racial capitalist domination. Rooted in Black geographies, this special issue asks what fugitivity—as a historical phenomenon, analytical category, and political practice—adds to our understanding of the production of space and subjects today. As a method, fugitivity travels across disciplinary boundaries and multiple spacetimes, charting the entanglements of geographies of racial violence and the freedom practices of racialized people. The articles in the special issue are unified by a concern for how fugitivity, as a method of knowledge-making, kin-making, and place-making, elude the enclosure of traditional politics and how collective, rather than individual, resistances forge alternative spaces in excess but never fully outside of dominant geographies.